2021
DOI: 10.2196/31649
|View full text |Cite
|
Sign up to set email alerts
|

Usability Evaluation of an Offline Electronic Data Capture App in a Prospective Multicenter Dementia Registry (digiDEM Bayern): Mixed Method Study

Abstract: Background Digital registries have been shown to provide an efficient way of gaining a better understanding of the clinical complexity and long-term progression of diseases. The paperless method of electronic data capture (EDC) during a patient interview saves both time and resources. In the prospective multicenter project “Digital Dementia Registry Bavaria (digiDEM Bayern),” interviews are also performed on site in rural areas with unreliable internet connectivity. It must be ensured that EDC can … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 93 publications
0
6
0
Order By: Relevance
“…An innovative approach used in this study is the usability and functionality evaluation of the online solution by using technological tools (smartphone and tablet for telephone and/or video-call), which reported very high values in the I-IG patients. These results could be compared to the results of other studies [33,34] that reported high user satisfaction scores for online health services.…”
Section: Discussionmentioning
confidence: 86%
“…An innovative approach used in this study is the usability and functionality evaluation of the online solution by using technological tools (smartphone and tablet for telephone and/or video-call), which reported very high values in the I-IG patients. These results could be compared to the results of other studies [33,34] that reported high user satisfaction scores for online health services.…”
Section: Discussionmentioning
confidence: 86%
“…Although the SUS score in this study was slightly lower than the average score of 68 for health care apps [ 38 ], it was maintained at above 50 points. In addition, the extracted usability issues were fewer than those in previous surveys [ 21 , 39 ] because we had conducted a preliminary test. The iterative usability evaluation strategy appeared to be effective.…”
Section: Discussionmentioning
confidence: 99%
“…The version of Lohmann and Schäffer is used in different projects to measure their users satisfaction or the usability of their system [19,20]. The German translation of Gao et al was used for example to evaluate the usability of a data capture app [21] or to determine the feasibility of exergames in rehabilitation [22].…”
Section: Discussionmentioning
confidence: 99%